Kepemimpinan Kiai dalam Transformasi Pendidikan Islam (Studi Atas Perilaku Kepemimpinan Kiai dalam Mengelola Pondok Pesantren di Situbondo) - Sulaiman Sulaiman (STAIFAS-Press, 2016)
Teacher of Islam represent religious leader taken as peer by society around. Peer in many matter it is of course, like spiritual tuition, including also as place to consult, to asking for message, asking for religion discourse and others. But in many matter, frequent teacher of Islam of times; rill made by focus, included in solution about Muslim boarding school, education of Islam. This Condition later; then express that Muslim boarding school as subculture in society not merely rendering intellectual human being, more than anything elseÂ teacher of Islam as founder, custodian and preserver of Muslim boarding school also represent one who at the same time grad (output) of world education of Muslim boarding school. Â Kata Kunci: Perilaku Kepemimpinan Kiai, Transformasi Pendidikan Islam, Mengelola Pondok Pesantren